Question
upstudy study bank question image url

\( p: 2 p+2: 5 p+3: \ldots \) are the first three terms of an arithmetic sequen (a) Calculate the value of \( p \). (b) Determine the sequence. (c) Find the 49 th term. (d) Which term of the sequence is \( 100 \frac{1}{2} \) ?

Ask by Potter Chen. in South Africa
Jan 31,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(a) \( p = \frac{1}{2} \) (b) The sequence is \( \frac{1}{2}, \, 3, \, 5.5, \, \ldots \) with a common difference of \( \frac{5}{2} \). (c) The 49th term is \( 120.5 \). (d) \( 100 \frac{1}{2} \) is the 41st term.

Solution

Let's analyze the arithmetic sequence \( p, \, 2p + 2, \, 5p + 3, \ldots \) and solve each part step by step. ### (a) Calculate the value of \( p \) In an arithmetic sequence, the difference between consecutive terms is constant. Let's denote this common difference by \( d \). Given the first three terms: 1. \( a_1 = p \) 2. \( a_2 = 2p + 2 \) 3. \( a_3 = 5p + 3 \) The common difference \( d \) can be calculated as: \[ d = a_2 - a_1 = (2p + 2) - p = p + 2 \] \[ d = a_3 - a_2 = (5p + 3) - (2p + 2) = 3p + 1 \] Setting the two expressions for \( d \) equal to each other: \[ p + 2 = 3p + 1 \] \[ 2 - 1 = 3p - p \] \[ 1 = 2p \quad \Rightarrow \quad p = \frac{1}{2} \] **Answer:** \( p = \frac{1}{2} \) ### (b) Determine the sequence With \( p = \frac{1}{2} \), let's find the first few terms and establish the general formula. 1. \( a_1 = p = \frac{1}{2} \) 2. \( a_2 = 2p + 2 = 2 \times \frac{1}{2} + 2 = 1 + 2 = 3 \) 3. \( a_3 = 5p + 3 = 5 \times \frac{1}{2} + 3 = \frac{5}{2} + 3 = \frac{11}{2} = 5.5 \) The common difference \( d \) is: \[ d = 3 - \frac{1}{2} = \frac{5}{2} = 2.5 \] The general term \( a_n \) of the sequence can be expressed as: \[ a_n = a_1 + (n - 1)d = \frac{1}{2} + (n - 1) \times \frac{5}{2} = \frac{5n - 4}{2} \] **Answer:** The sequence is given by \( a_n = \frac{5n - 4}{2} \). The first few terms are \( \frac{1}{2}, \, 3, \, 5.5, \, \ldots \) with a common difference of \( \frac{5}{2} \). ### (c) Find the 49th term Using the general formula: \[ a_{49} = \frac{5 \times 49 - 4}{2} = \frac{245 - 4}{2} = \frac{241}{2} = 120.5 \] **Answer:** The 49th term is \( 120.5 \) or \( 120 \frac{1}{2} \). ### (d) Which term of the sequence is \( 100 \frac{1}{2} \)? We need to find \( n \) such that: \[ a_n = 100.5 = \frac{5n - 4}{2} \] Multiply both sides by 2: \[ 5n - 4 = 201 \] Add 4 to both sides: \[ 5n = 205 \] Divide by 5: \[ n = 41 \] **Answer:** \( 100 \frac{1}{2} \) is the 41st term of the sequence.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the given arithmetic sequence, we start with the terms: 1. The first term is \( p \). 2. The second term is \( 2p + 2 \). 3. The third term is \( 5p + 3 \). ### (a) Calculate the value of \( p \). In an arithmetic sequence, the difference between consecutive terms is constant. Therefore, the difference between the second term and the first term should equal the difference between the third term and the second term: \[ (2p + 2) - p = (5p + 3) - (2p + 2) \] Calculating both sides gives: \[ p + 2 = 3p + 1 \] Now, rearranging this equation: \[ p + 2 - 1 = 3p \] \[ 1 = 3p - p \] \[ 1 = 2p \] \[ p = \frac{1}{2} \] ### (b) Determine the sequence. Using \( p = \frac{1}{2} \): 1. First term: \( p = \frac{1}{2} \) 2. Second term: \( 2p + 2 = 2(\frac{1}{2}) + 2 = 1 + 2 = 3 \) 3. Third term: \( 5p + 3 = 5(\frac{1}{2}) + 3 = \frac{5}{2} + 3 = \frac{5}{2} + \frac{6}{2} = \frac{11}{2} \) Now calculating the common difference: \[ 3 - \frac{1}{2} = \frac{6}{2} - \frac{1}{2} = \frac{5}{2} \] \[ \frac{11}{2} - 3 = \frac{11}{2} - \frac{6}{2} = \frac{5}{2} \] Thus, the sequence is: \( \frac{1}{2}, 3, \frac{11}{2}, \ldots \) ### (c) Find the 49th term. The \( n \)-th term of an arithmetic sequence can be calculated using the formula: \[ a_n = a_1 + (n - 1)d \] Where \( a_1 = \frac{1}{2} \) and \( d = \frac{5}{2} \): \[ a_{49} = \frac{1}{2} + (49 - 1)\frac{5}{2} \] \[ = \frac{1}{2} + 48 \cdot \frac{5}{2} \] \[ = \frac{1}{2} + \frac{240}{2} \] \[ = \frac{241}{2} \] ### (d) Which term of the sequence is \( 100 \frac{1}{2} \)? First, convert \( 100 \frac{1}{2} \) to an improper fraction: \[ 100 \frac{1}{2} = 100.5 = \frac{201}{2} \] We set this equal to the \( n \)-th term formula: \[ \frac{201}{2} = \frac{1}{2} + (n - 1) \frac{5}{2} \] Isolate \( n \): \[ \frac{201}{2} - \frac{1}{2} = (n - 1) \frac{5}{2} \] \[ \frac{200}{2} = (n - 1) \frac{5}{2} \] \[ 100 = (n - 1) \cdot \frac{5}{2} \] Multiplying through by \( 2 \): \[ 200 = 5(n - 1) \] \[ 40 = n - 1 \] \[ n = 41 \] Thus, \( 100 \frac{1}{2} \) is the \( 41^{st} \) term of the sequence.

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy